Doctor in the lab: what is it like for a doctor to work with scientists? - Jorm, C. M. (BMJ Group, 1996)
As clinical academic medical departments strive to improve the quality of their research, clinicians and scientists are forced into closer liaison. In many cases, clinical departments now have research laboratories directed by "basic scientists" but often staffed, in part at least, by doctors. To someone who has not worked in one, these laboratories may seem uncompromising and forbidding work environments. This article presents a "case report" written from the viewpoints of the doctor, the scientist, and the professor.